UJI TOKSISITAS AKUT DARI EKSTRAK KULIT BUAH RAMBUTAN (Nepheliumlappaceum L.) YANG BERPOTENSI SEBAGAI OBAT HERBAL ANTIDIABETES - Muhtadi -; Haryoto -; Tanti Azizah Sujono; Andi Suhendi (Universitas Muhammadiyah Semarang, 2015)
The acutetoxicitytestinghave been conducted inthe male and female ratsSD strain oframbutan (Nepheliumlappaceum L.)fruitpeel extract. The testing had been doneby providingwitha doserankedasfollows: the firstdose; 0mg/kgBW, doseII; 400mg/kgBW, doseIII; 1,400mg/kgBW, IVdoses; 4,900mg/kgBW, and thedosage ofV; 17,150mg/ kgBW for 14days. Thenit had been observedclinical symptomsthat happened, changed in body weightperweekanddefect on vital organs, namely: the liver, kidneys, stomach, intestines, spleen, heartandlungs. Theresults ofthis study was concludedthat thehighest doseof up to17,150mg/kgBW ofthe extract, safety andproved to be not toxic to thefemaleandmaleratsSDstrain.Keywords : The acutetoxicitytesting; rambutanfruitpeel extract; thefemaleandmaleratsSDstrain.